Acinetobacter seifertii Isolated from China: Genomic Sequence and Molecular Epidemiology Analyses. Issue 9 (March 2016) - Yang, Yunxing; Wang, Jianfeng; Fu, Ying; Ruan, Zhi; Yu, Yunsong
Abstract : Abstract: Clinical infections caused by Acinetobacter spp. have increasing public health concerns because of their global occurrence and ability to acquire multidrug resistance. Acinetobacter calcoaceticus – Acinetobacter baumannii (ACB) complex encompasses A. calcoaceticus, A. baumannii, A. pittii (formerly genomic species 3), and A nosocomial (formerly genomic species 13TU), which are predominantly responsible for clinical pathogenesis in the Acinetobacter genus. In our previous study, a putative novel species isolated from 385 non- A. baumannii spp. strains based on the rpoB gene phylogenetic tree was reported. Here, the putative novel species was identified as A. seifertii based on the whole-genome phylogenetic tree. A. seifertii was recognized as a novel member of the ACB complex and close to A. baumannii and A. nosocomials. Furthermore, we studied the characteristics of 10 A. seifertii isolates, which were distributed widely in 6 provinces in China and mainly caused infections in the elderly or children. To define the taxonomic status and characteristics, the biochemical reactions, antimicrobial susceptibility testing, pulsed field gel electrophoresis (PFGE), multilocus sequence typing (MLST), and whole-genome sequence analysis were performed. The phenotypic characteristics failed to distinguish A. serfertii from other species in the ACB complex. Most of the A. seifertii isolates were susceptible to antibiotics commonly used for nosocomial Acinetobacter spp. infections, but one isolate (strain A362) was resistant to ampicillin/sulbactam, ceftazidime and amikacin. The different patterns of MLST and PFGE suggested that the 10 isolates were not identical and lacked clonal relatedness. Our study reported for the first time the molecular epidemiological and genomic features of widely disseminated A. seifertii in China. These observations could enrich the knowledge of infections caused by non- A. baumannii and may provide a scientific basis for future clinical treatment.